Characterization of Out-of-Plane wrinkles in woven CFRP Laminate: Development of a novel algorithm utilizing ultrasonic scan data - Admay Amif, Md; Khan, Irrtisum; Jack, David A. (Composites. Part A, Applied science and manufacturing, 2025)
•Development of a novel algorithm for characterizing out-of-plane wrinkles in woven CFRP laminates.•Precise quantification and spatial analysis through three-dimensional lamina by lamina extraction.•Two-dimensional wrinkle attributes validated against microscopy from sectioned samples.•Improvement in analyzing conventional ultrasound data to enhance non-destructive testing capabilities. Out-of-plane wrinkles in laminated composites reduce the structural integrity. This study presents an algorithm to characterize wrinkle height and intensity of each lamina within a plain weave laminated composite, utilizing full waveform ultrasonic scan data. This algorithm enables the extraction of individual laminae in three dimensions. An immersion tank ultrasound testing system is employed for scanning coupled with a 7.5 MHz spherically focused transducer. Surface construction from the waveform entails a spatial Gaussian averaging followed by a tracking of voltage peaks in time of individual A-scans, from which we extract individual lamina interfaces. Four samples are presented with various wrinkle amplitudes encompassing a wide range of industrially relevant scenarios. The comparison of the ultrasonically characterized wrinkle heights with microscopic images of sectioned samples demonstrates consistency between the two methods, with a maximum deviation of 0.06 mm wrinkle amplitude across all samples considered in this study.